PENGARUH V ARIASI PEMASANGAN HEAT EXCHANGERSPADAREFRIGERATORTERHADAP KAPASIT AS PENDINGINAN DAN LAJU ALIRAN MASSA REFRIGERAN - Berman, Ega Taqwali (JURNAL PENELITIAN SAINTIKA, 2011)
This study aims to compare the effect of variations in the refrigerator heat exchanger installation ofcooling capacity and refrigerant mass flow rate. Tests performed on the test section consists of twotypes of heat exchangers, Suction-Liquid Heat Exchanger (SLHX) and Tube in Tube Heat Exchanger(TiTHX). Test data measured at the temperature of the cooling load temperature of 60C to - 60C andthe working fluid is used as a cooling medium is a refrigerant 12. As a result, it was obtained that inthis research was cooling capacity by a refrigeration system that uses TiTHX 0.6% greater than therefrigeration system that uses SLHX. This is due to there is little difference between the temperature ofevaporation and temperature liquid refrigerant that will go into the expansion device on a system thatuses TiTHX than refrigeration systems that use SLHX. The amount of refrigerant is circulated 0.6%less on a system that uses TiTHX than systems that use SLHX.